The permeability of SPION over an artificial three-layer membrane is enhanced by external magnetic field - Ge Xianxi; Kopke Richard D; Kropp Bradley; Zhang Yuan; Mondalek Fadee G; Jackson Ronald L; Dormer Kenneth J (Journal of Nanobiotechnology, 2006)
Abstract Background Sensorineural hearing loss, a subset of all clinical hearing loss, may be correctable through the use of gene therapy. We are testing a delivery system of therapeutics through a 3 cell-layer round window membrane model (RWM model) that may provide an entry of drugs or genes to the inner ear. We designed an in vitro RWM model similar to the RWM (will be referred to throughout the paper as RWM model) to determine the feasibility of using superparamagnetic iron oxide (Fe3O4) nanoparticles (SPION) for targeted delivery of therapeutics to the inner ear. The RWM model is a 3 cell-layer model with epithelial cells cultured on both sides of a small intestinal submucosal (SIS) matrix and fibroblasts seeded in between. Dextran encapsulated nanoparticle clusters 130 nm in diameter were pulled through the RWM model using permanent magnets with flux density 0.410 Tesla at the pole face. The SIS membranes were harvested at day 7 and then fixed in 4% paraformaldehyde. Transmission electron microscopy and fluorescence spectrophotometry were used to verify transepithelial transport of the SPION across the cell-culture model. Histological sections were examined for evidence of SPION toxicity, as well to generate a timeline of the position of the SPION at different times. SPION also were added to cells in culture to assess in vitro toxicity. Results Transepithelial electrical resistance measurements confirmed epithelial confluence, as SPION crossed a membrane consisting of three co-cultured layers of cells, under the influence of a magnetic field. Micrographs showed SPION distributed throughout the membrane model, in between cell layers, and sometimes on the surface of cells. TEM verified that the SPION were pulled through the membrane into the culture well below. Fluorescence spectrophotometry quantified the number of SPION that went through the SIS membrane. SPION showed no toxicity to cells in culture. Conclusion A three-cell layer model of the human round window membrane has been constructed. SPION have been magnetically transported through this model, allowing quantitative evaluation of prospective targeted drug or gene delivery through the RWM. Putative in vivo carrier superparamagnetic nanoparticles may be evaluated using this model.